Realitas Kehidupan dalam Perspektif Antropologis - Mudjahirin Thohir (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
to be able to live normally, human being struggle to fulfill their basic needs. The human basic needs are: biological, social, and integrative. Biological needs include: food, clothing, and shelter. Social needs include: interact, cooperate, compete, and social order. Integrative needs include the need for: freedom in justice in accordance with the agreed common reference. So that regularity of life is realized, then guidelines are needes that are concidered true and good. There are five types of guidelines as a reference, namely: constitutive faith, cognitive, evaluative, ethical, and expressive. This is a reference as the ideal culture of society. Although there are such guidelines, but in real practice (real clture) violations often occur, including because of individual or group interest. As in ilustraton, it can be seen in the world of football, the concept of fairplay is manifested in the form of inappropriate actions. Not to mention in the political and economic world. From this angle the concepts of fairness and justice are always warmly studied. This paper discusses about it from the social sciences perspective, especially anthropology. Keywords: Basic need; guideline; ideal culture; real culture; fairplay. Intisari Untuk dapat hidup secara normal, manusia berjuang untuk memenuhi kebutuhan dasarnya. Kebutuhan-kebutuhan dasar itu ialah kebutuhan biologis, sosial, dan integratif. Kebutuhan biologis meliputi pangan, sandang, dan papan. Kebutuhan sosial meliputi kebutuhan berinteraksi, bekerjasama, dan bersaing. Kebutuhan integratif meliputi nilai-nilai, agar kegiatan bekerja sama maupun bersaing didasari oleh koridor nilai-nilai dan norma hukum yang adil. Untuk dapat memenuhi kebutuhan dasar tersebut, secara ideal (ideal culture) masyarakat manusia memerlukan pedoman yang dianggap benar dan baik. bermuara kepada lima acuan, yaitu: konstitutif, kognitif, evaluatif, etik, dan ekspresif. Meskipun sudah ada pedoman, tetapi dalam kebudayaan riil (real culture) yakni dalam tataran praktik kehidupan, pedoman-pedoman tadi sering dilanggarnya. Dari sinilah nilai dan norma-norma hukum, hampir selalu menjadi ajang perdebatan, sebagaimana ilustrasi konsep fair play dalam pertandingan sepakbola. Tulisan ini mendiskusikan mengenai persoalan adil dan keadilan sosial ditinjau dari perspektif antropologis. Kata kunci: Kebutuhan dasar; acuan; budaya ideal; budaya riil; fairplay.